A Clinical Study of Intensity-Modulated Radiotherapy-Induced Dry Eye Disease in Head and Neck Malignancies - Monga, Ashima; Thatte, Shreya; Goyal, Yashas (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2022)
Context: Dry Eye Disease is a multifaceted disorder caused by a variety of factors ranging from age to demographic profile. Radiation-induced dry eye disease is a relatively unexplored domain of this disease. Aim: To explore the various factors contributing to dry eye disease in patients receiving radiation therapy for head and neck malignancies with a fixed dose and duration of radiotherapy. Settings and design: A cross-sectional study conducted at a tertiary healthcare centre during a period of 1 year. Method and material: The study included 101 patients with head and neck malignancies who received a 60-Gray (Gy) dose of radiotherapy over a duration of 30 weeks. Patients were evaluated for signs and symptoms of dry eye on day 30 after completing their radiotherapy cycles using slit lamp biomicroscopy and various other tests for dry eye and compared with age, gender, location of malignancy, and adjunctive chemotherapy. Results: Out of a total of 101 patients, 45% had mild dry eye disease. 44–45% of mild dry eye disease was seen in the age groups of 20–50 and 51–80 years. The incidence of mild-to-moderate dry eye disease was almost similar (47% and 50 %) in both genders. The incidence of severe dry eye was seen in only 1% of patients. Dry eye disease was more severe in malignancies located closer to the orbit. The use of cisplatin as an adjunctive chemotherapy agent proved to be a risk factor for dry eye disease. Conclusion: Intensity-modulated radiotherapy is not enough to prevent the development of dry eye disease. A close and strict follow-up with an opthalmologist is essential for its prevention and early management.